Предмет: Алгебра, автор: anna25251

упростите выражение 2b^2-b/b^3+1 - b-1/b^2-b+1

Ответы

Автор ответа: axatar
23

Ответ:

\tt \displaystyle \frac{1}{b+1}

Объяснение:

\tt \displaystyle \frac{2 \cdot b^2-b}{b^3+1}-\frac{b-1}{b^2-b+1} = \frac{2 \cdot b^2-b}{(b+1) \cdot (b^2-b+1)}-\frac{b-1}{b^2-b+1} =\\\\= \frac{2 \cdot b^2-b}{(b+1) \cdot (b^2-b+1)}-\frac{(b-1) \cdot (b+1)}{(b+1) \cdot (b^2-b+1)} = \\\\= \frac{2 \cdot b^2-b-(b-1) \cdot (b+1)}{(b+1) \cdot (b^2-b+1)}= \frac{2 \cdot b^2-b-(b^2-1)}{(b+1) \cdot (b^2-b+1)}=

\tt \displaystyle = \frac{2 \cdot b^2-b-b^2+1}{(b+1) \cdot (b^2-b+1)}=\frac{b^2-b+1}{(b+1) \cdot (b^2-b+1)}=\frac{1}{b+1} .

Похожие вопросы
Предмет: Математика, автор: KatiaKlep1